Pengaruh Terapi Bermain FlashcardUntuk Meningkatkan Interaksi Sosial Pada Anak Autis di Miracle Centre Surabaya - T, Dinar Rapmauli; Matulessy, Andik (Persona:Jurnal Psikologi Indonesia, 2015)
This study aimed to determine the effect of play therapy flashcard to increase social interaction of children with autism in the Miracle Centre Surabaya. Characteristics of research subjects include autistic children aged 2-5 years. The number of subjects of this study as many as six children, in addition to the informant therapists / teachers. The results showed that obedience dimensional eye contact before flashcard therapy has an overall average of 0.333 on average increased to 0.75. Z value of -2.032 with a significant support of 0.042, these results indicate significant. At dimensional mimicked the overall average value of 0.315 increased to 0.667. Z value of -1.363 with the support of 0.173 significance, the results showed no significance. Receptive language dimension overall average value of 0, 288 increased to 0.689. Z of -2.201 with the support of 0,028 significance, these results indicate significant. Dimensional expressive language overall average value of 0.250 increased to 0.583. Z value of -1.841 to 0.066 signifinakansi support, these results indicate insignificant. From the results of this study concluded that the play therapy flashcard effect to improve eye contact, and receptive language skills but less perpengaruh on the ability of imitation (mimic) and expressive language skills.